Arbitrary segments of absolute negative mobility. (9th January 2017) - Chen, Ruyin; Nie, Linru; Chen, Chongyang; Wang, Chaojie
Abstract: In previous research work, investigators have reported only one or two segments of absolute negative mobility (ANM) in a periodic potential. In fact, many segments of ANM also occur in the system considered here. We investigate transport of an inertial particle in a gating ratchet periodic potential subjected to a constant bias force. Our numerical results show that its mean velocity can decrease with the bias force increasing, i.e. ANM phenomenon. Furthermore, the ANM can take place arbitrary segments, even up to more than thirty. Intrinsic physical mechanism and conditions for arbitrary segments of ANM to occur are discussed in detail.